SEGMENTS OF AUDIENCES AND TARGETING OPPORTUNITIES IN GOOGLE ADS - HOLUBOVSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the features of using the Google Ads as a program for Internet marketing. The number of online users is growing every year in the world and in Ukraine. People spend more time online than in any shopping mall, financial institution, leisure facility, etc. That's why using of Google Ads to promote products, services and businesses has become an integral part of a successful advertising campaign. As a rule, Internet marketing specialists are engaged in researching the application possibilities of Google Ads from different digital-agencies. Scientists usually focus their attention on the definition of “Internet marketing”, “Digital-marketing” etc. That's why we're exploring the features of targeting in Google Ads based on a tool from a practical perspective.This article also substantiates the importance and value of using Google Ads to promote goods and services. The main audience segments for targeting, which are available in Google Ads, are defined and structured in the article. Four groups of segments were identified: Google segments, Data segments (information from website, mobile application, YouTube, database and lal-audience, Custom segments, Combined segments.By demographic characteristics, Google Ads gives an opportunity to choose targeting based on age, gender, family income, marital status, presence of children, education and others. An important part of running ads in Google Ads is selecting geotargeting. It can be a country, city, district or radius location. Equally important is the choice of devices on which advertising will be displayed - computers, tablets, smartphones, TVs. Google Ads also provides an opportunity to target users of specific mobile operators. All of these features form a significant advantage of Google Ads over other tools.
Keywords: Google Ads; targeting; target audience; affinity segments; geotargeting; demographic targeting